2009
DOI: 10.1186/1756-8722-2-44
|View full text |Cite
|
Sign up to set email alerts
|

The transplant iron score as a predictor of stem cell transplant survival

Abstract: Recent studies have suggested that the presence of iron overload prior to stem cell transplantation is associated with decreased survival. Within these studies, the criteria used to define iron overload have varied considerably. Given the lack of consensus regarding the definition of iron overload in the transplant setting, we sought to methodically examine iron status among transplant patients. We studied 78 consecutive patients at risk for transfusion-related iron overload (diagnoses included AML, ALL, MDS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
0
41
2
2
Order By: Relevance
“…10 Iron overload prior to transplant has been suggested to predispose to a higher rate of lethal infections. 19,23 International Journal of Hematology and Oncology A higher threshold of pre-transplant serum ferritin levels may predict HSCT outcomes. 27 Pretransplantation serum ferritin may have significant prognostic value in patients with MDS undergoing myeloablative allogeneic HSCT, inducing a significant increase of non-relapse mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Iron overload prior to transplant has been suggested to predispose to a higher rate of lethal infections. 19,23 International Journal of Hematology and Oncology A higher threshold of pre-transplant serum ferritin levels may predict HSCT outcomes. 27 Pretransplantation serum ferritin may have significant prognostic value in patients with MDS undergoing myeloablative allogeneic HSCT, inducing a significant increase of non-relapse mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Iron overload may predispose to a higher rate of infections associated with transplantation. [19][20][21][22][23] Stem cell sources, distinct diseases and different protocols may also affect the impact of iron overload on the process of transplantation. [24][25][26][27][28] Unfortunately, some of the studies evaluating iron overload in transplant setting did not precisely show the patients with iron overload, mainly due to ignoring consideration of transferrin saturation along with hyperferritinemia for elimination of non-iron overload etiologies of hyperferritinemia (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Za wysoki "wskaźnik żelazowy" uznano jego wartość powyżej 2. Wskaźnik ten jest predyktorem przeżycia chorych po allo-HSCT -im jest wyż-szy, tym większe jest ryzyko zgonu [13]. Według Lim i wsp.…”
Section: Konsekwencje Kliniczne Przeładowania Organizmu żElazemunclassified
“…Nonetheless, the majority of aplastic patients in these studies tended to have high ferritin levels or high aggregate "iron scores" at a level the reports associated with increased 100-day mortality, acute GVHD occurrence, bacteremia/infection, and decreased overall survival. 47,48 However, the associations between iron overload and adverse outcomes observed may be skewed by the prevailing myelodysplasia diagnosis in the study cohorts, and this and other confounding factors may contribute to these observed outcomes. There is as yet no data in aplastic anemia that directly address the value of chelation-related decreases in iron compared with the natural presentation to HSCT with less iron-loaded status.…”
Section: Alternative Donor Hsctmentioning
confidence: 99%